Effect of nanoparticle size and concentration on boiling performance of SiO2 nanofluid. (April 2017) - Hu, Yanwei; Li, Haoran; He, Yurong; Liu, Ziyu; Zhao, Yunhua
Highlights: Pool BHT characteristics of SiO2 -EG/DW nanofluids are experimentally investigated. HTC increases with decreasing the nanoparticle diameter from 120 nm to 84 nm. The enhancement of HTC reaches maximum at 0.25 vol%, then decreases with the increase of SiO2 concentration. Probable mechanism due to nanoparticle coating is qualitatively analyzed. Abstract: The suspension of nanoparticles into transitional heat-transfer media could be an alternative to conventional fluids. The present work experimentally investigates the boiling heat-transfer characteristics of ethylene glycol (EG) and water (H2 O) mixture based SiO2 nanofluid under realistic conditions. An EG aqueous solution with a volume fraction of 60% was used as the base fluid owing to its perfect freeze-proofing performance. Stable nanofluids were formulated through magnetic stirring and ultrasonic treatment and the effect of the nanoparticle size and concentration on the boiling characteristics of the nanofluids were considered. The results show that the boiling heat-transfer coefficient (HTC) increased when decreasing the nanoparticle diameter from 120 nm to 84 nm. In addition, with the increase of nanoparticle concentration, the HTC first increased rapidly and then exhibited negative growth in the concentration range 0.25–1.00%. Moreover, the HTC deteriorated for nanoparticle volume fractions above 0.75%. Based on the experimental results, the probable mechanism of the boiling heat transfer caused by the nanoparticle coating is qualitatively analyzed.